FAMOUS PEOPLE OF GREAT BRITAIN IN ART - Qosimova Muslimaxon; Abdurakhmanov Turakhon Saydullayevich (TADQIQOTLAR, 2025)
Annotation:This  article  provides  an  in-depth  analysis  of  some  of  the  most influential British artists who have shaped the world of art. It explores their artistic styles,  notable  works,  and  contributions  to  movements  such  as  Romanticism, Modernism, and Pop Art. The article also examines the historical and cultural impact of these artists, their influence on subsequent generations, and their contributions to global artistic traditions.